Detection of SARS-CoV-2 Specific Antibodies in Saliva Samples - Yu, Siyang; Zhang, Peiyan; Liao, Mingfeng; Zhang, Juanjuan; Luo, Suisui; Zhai, Jinglei; Zhang, Yaxi; Lin, Jingyan; Yuan, Jing; Zhang, Zheng; Wang, Fuxiang; Wei, Lanlan (Frontiers in Immunology, 2022)
Molecular assays on nasopharyngeal swabs act as the confirmatory test in CoronaVirus Disease (COVID-19) diagnosis. However, technical requirement of nasopharyngeal sampling and molecular assays limit the testing capabilities. Recent studies suggest the use of saliva for COVID-19 diagnostic test. In this study, a total of 44 patients diagnosed with COVID-19 in The Third People’s Hospital of Shenzhen were enrolled. Saliva specimens and serum specimens were obtained at different time points and the immunoglobulins against SARS-CoV-2 were measured. The results showed that saliva IgA presented higher COI value than IgG and IgM. In matched saliva and serum samples, all saliva samples presented lower IgG level than serum samples, and only one saliva sample presented higher IgM level. The conversion rates of saliva IgA and the detection of viral nucleic acid were analyzed in the first and second week after hospitalization. The positive rates increased when combining saliva IgA and viral nucleic acid detection. In conclusion, our results provide evidence that saliva IgA could serve as useful index for early diagnosis of COVID-19.